On asymptotic approximation of a solution of a boundary-value problem for a nonlinear nonautonomous equation - Sokil, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
On the basis of periodic Ateb functions, in the resonance and nonresonance cases, we construct the asymptotic approximation of one-frequency solutions of a boundary-value problem for a nonlinear nonautonomous equation.